Dapagliflozin in Heart Failure with Mildly Reduced or Preserved Ejection Fraction - Solomon, Scott D; McMurray, John J V; Claggett, Brian; de Boer, Rudolf A; DeMets, David; Hernandez, Adrian F; Inzucchi, Silvio E; Kosiborod, Mikhail N; Lam, Carolyn S P; Martinez, Felipe; Shah, Sanjiv J; Desai, Akshay S; et al. (The New England journal of medicine, 2022)
BACKGROUND: Sodium-glucose cotransporter 2 (SGLT2) inhibitors reduce the risk of hospitalization for heart failure and cardiovascular death among patients with chronic heart failure and a left ventricular ejection fraction of 40% or less. Whether SGLT2 inhibitors are effective in patients with a higher left ventricular ejection fraction remains less certain. METHODS: We randomly assigned 6263 patients with heart failure and a left ventricular ejection fraction of more than 40% to receive dapagliflozin (at a dose of 10 mg once daily) or matching placebo, in addition to usual therapy. The primary outcome was a composite of worsening heart failure (which was defined as either an unplanned hospitalization for heart failure or an urgent visit for heart failure) or cardiovascular death, as assessed in a time-to-event analysis. RESULTS: Over a median of 2.3 years, the primary outcome occurred in 512 of 3131 patients (16.4%) in the dapagliflozin group and in 610 of 3132 patients (19.5%) in the placebo group (hazard ratio, 0.82; 95% confidence interval [CI], 0.73 to 0.92; P<0.001). Worsening heart failure occurred in 368 patients (11.8%) in the dapagliflozin group and in 455 patients (14.5%) in the placebo group (hazard ratio, 0.79; 95% CI, 0.69 to 0.91); cardiovascular death occurred in 231 patients (7.4%) and 261 patients (8.3%), respectively (hazard ratio, 0.88; 95% CI, 0.74 to 1.05). Total events and symptom burden were lower in the dapagliflozin group than in the placebo group. Results were similar among patients with a left ventricular ejection fraction of 60% or more and those with a left ventricular ejection fraction of less than 60%, and results were similar in prespecified subgroups, including patients with or without diabetes. The incidence of adverse events was similar in the two groups. CONCLUSIONS: Dapagliflozin reduced the combined risk of worsening heart failure or cardiovascular death among patients with heart failure and a mildly reduced or preserved ejection fraction. (Funded by AstraZeneca; DELIVER ClinicalTrials.gov number, NCT03619213.).
Keywords: benzhydrylové sloučeniny; tepový objem; Stroke Volume; glukosidy; Diabetes Mellitus, Type 2; Glucosides; Benzhydryl Compounds; Humans; Sodium-Glucose Transporter 2 Inhibitors; funkce levé komory srdeční; diabetes mellitus 2. typu; Heart Failure; glifloziny; lidé; Ventricular Function, Left; srdeční selhání